ANALISIS KETERAMPILAN BERBICARA SISWA KELAS V PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Yulia Maulani; Nur Azmi Alwi; Lindri Marthinopa; Nadiah Syaidah (Cerdas Proklamator, 2021)
Speaking skill is one of the four language skills that are important to master. Because speaking skills are an important element in communicating, so that students can convey messages and ideas well. The purpose of this study is [1] to determine the speaking skills of 5th grade students of SDN 01 TARANTANG [2] To assist in making speaking skills teaching materials based on the results of the analysis of 5th grade students' speaking skills of SDN 01 TARANTANG. The research approach used in this research is descriptive qualitative research with analytical methods. With data collection techniques through oral tests and literature studies. Based on the results of the analysis that has been carried out by researchers on 5th grade elementary school students, it can be seen that the average score of students' scores is 60 with the provision that 3 students have the highest scores such as KPA, SO, WSP by getting an overall score of 91, then for the lowest score, namely PI, TR, WFR with an overall score of 33, the reason is that they did not take the exam at all and did not answer the questions given by the researcher.